Household financial literacy and relative poverty: An analysis of the psychology of poverty and market participation - Wang, Shanping; Cao, Peng; Huang, Shao (Frontiers in Psychology, 2022)
Financial literacy is the significant human capital factor affecting people’s ability to obtain financial services. Evaluating the relationship between financial literacy and relative poverty is of great significance to poverty reduction. This study investigated the impacts of financial literacy on relative poverty from the perspective of poverty psychology and market participation using data from the 2017, 2019 China Household Finance Survey (CHFS). The empirical findings showed that financial literacy can alleviate relative household poverty through household participation in entrepreneurial activities, commercial insurance participation and the choice of lending channels. Financial literacy has significant poverty reduction effect on households of continuous operation, reduces the likelihood of exiting operation. Further discussion showed that the poverty reduction effect of financial literacy is more pronounced among households with higher levels of financial literacy, under the age of sixty, low levels of indebtedness and in the eastern region. Our study provides empirical evidence for encouraging market participation and promoting financial literacy and provide valuable recommendations for the policymaker to improve poverty reduction effect in the developing country context.